Power-law scaling of sub-coercive field dynamic hysteresis response in 0.7Pb(Zr1/2Ti1/2)O3-0.3Pb(Zn 1/3Nb2/3)O3 ceramic - R. Yimnirun (2018)
Scaling behaviour of sub-coercive field dynamic ferroelectric hysteresis under the influence of stress was investigated in rhombohedral 0.7PZT-0.3PZN bulk ceramic. The scaling relation of hysteresis area 〈A〉 against frequency f, field amplitude E0 and stress σ for the minor loops takes the form of , which is very similar to that of soft and hard PZT ceramics. However, slightly faster responses to f and E0 indicate the ease of polarization orientation in this simpler domain structure ceramic as compared with commercial PZT ceramics. This study suggests that the domain structures play a significant role in controlling dynamic hysteresis behaviour of ferroelectric materials. © 2008 IOP Publishing Ltd.